Social media use and job choices: the mediating roles of work values and self-efficacy - Li, Fei; Shi, MinXuan; Feng, Ran (Frontiers in Psychology, 2025)
This study examines the association between social media use and college students’ employment choices, focusing on the roles of work values and self-efficacy as mediating factors. A survey of 254 college students in Anhui Province showed that social media users tended to have more flexible and diverse employment options than non-users. Regression analyses demonstrated a positive association between social media use and employment decisions, with work values and self-efficacy identified as mediating factors in this relationship. Notably, self-efficacy was found to enhance the association between work values and students’ employment choices. These findings suggest that fostering students’ self-efficacy enhances the positive impact of work values, emphasizing the need for career guidance to encourage appropriate use of social media while avoiding over-reliance. This study provides valuable insights into promoting full employment among college students by considering the role of social media in shaping their career decisions.